Standard HVM - Abbas G. (My University, 2025)
We discuss a standard hierarchical VEVs model which predicts the leptonic mixing angles in terms of the Cabibbo angle, and masses of strange and charm quarks as (Formula presented), and (Formula presented)for the normal mass ordering of neutrinos. This results in very precise predictions of the leptonic mixing angles given by (Formula presented), (Formula presented), and (Formula presented). Furthermore, we predict neutrinos to be the Dirac kind disfavoring the inverted mass hierarchy. The standard hierarchical VEVs model predicts a possible new class of the dark matter candidate, named as neutrinic dark matter. © 2025 World Scientific Publishing Company.